Fundamental studies on gelation of gelatin obtained from aquaculture food waste - Wen, Junzheng (Nanyang Technological University, 2022)
Gelatin is a valuable biopolymer with applications in many sectors. This research is to investigate the properties of microbial transglutaminase(MTG)-crosslinked fish gelatin. Extraction of gelatin was carried out on salmon skin and barramundi skin with acid-based method. FTIR was utilized to identify the composition of yield and determine whether it is gelatin as desired. Rheological studies were conducted with a focus on salmon gelatin. Amplitude sweep identified a LVR below 31% strain. Frequency sweep showed a clear distinction between storage modulus and loss modulus above 0.318 Hz. Time sweep showed a negative correlation between gelation time and MTG as well as gelatin concentration. Gelation time profile was also associated with MTG activity, where increased temperature from 5℃ to 50℃ led to increased enzyme activity as well as decreased gelation time. Beyond 50℃, MTG activity dropped and gelation time increased. Storage modulus of gel at the end of experiment run time was associated with gelation time and observed negative correlation. No observable physical crosslinking was identified in the experiment. In summary, this research explored a systematic characterization of gelatin gel properties, and determined the effect of certain parameters on the dynamic covalent crosslinking process of salmon gelatin. Further studies can be conducted to provide more thorough information on MTG-crosslinked fish gelatin.